Rethinking Digital Literacies and Learning - Elisabeth Hayes (Adult Education Research Conference, 2004)
Using concepts from the New Literacy Studies and theories of situated learning, along with an analysis of computer gaming, this paper argues for the need to rethink dominant views of adult literacies and learning in digital contexts.